Commerce des espèces sauvages menacées : les paradoxes de l’État vietnamien - Peter Bille Larsen; Marc Hufty; Chi Trung Tran; Sandra Gagnon (VertigO, 2016)
This article focuses on an often-neglected dimensions of Vietnam’s economic development : the deep crisis that threatens its biodiversity. Despite the priority given to economic growth, the biodiversity crisis is a growing concern both among the government and other key stakeholders. We examine the role played by the illegal wildlife trade, which greatly intensified since the the đổi mới reforms in the 1980s. Despite significant legal and administrative measures, the state appears unable to control the trade that has now taken on an international dimension. It is time to take a more thorough look at the regulatory practices. We address a factor overlooked by public policies themselves – the role of the state apparatus itself. In contrast to wider liberalization trends, the wildlife trade is on the paper governed by a centralized approach based on a command-and-control system. This is challenged by practices on the ground where informal trade is the norm governed through decentralized practices. Wildlife trade reveals a multitude of tensions : within the state apparatus ; between the center and the provinces ; between the country and its neighbors ; between the desire to control territory and the practices that escape such control ; and between the rationality of centralization and local realities. The wildlife trade illustrates challenges for governance, for the state monopoly over power, as well as for its capabilities of central coordination.